Utilization Of Gambir Leaf Extract (Uncaria gambir Roxb) As A Chicken Meat Preservative - Nasution, Nora Efrida (Jurnal Peternakan Integratif, 2021)
Gambier leaf extract is a latex extract from the leaves of the gambier plant and contains catechin compounds that act as antimicrobials. In order to increase the shelf life and minimize the use of synthetic chicken meat preservatives, this study was carried out with the aim of knowing the administration of gambir leaf extract (Uncaria gambir Roxb) as a chicken meat preservative. This study used a factorial 3 x 5 completely randomized design (CRD) with 3 replications. Factor I is various doses of gambir leaf extract, namely E1 (1% gambier leaf extract with aquadest solvent), E2 (1% gambier leaf extract with Castrol oil, tween and aquadest solvents), E3 (2% gambier leaf extract with Castrol oil solvent, tween and aquadest) and Factor II is the length of fermentation (1 day, 2 days, 3 days, 4 days and 5 days). Variables observed included air content (highest yield at concentration E2 = 77.56), Ph (highest yield at concentration E2 = 5.57), and total microbes (highest yield at concentration E = 7.73 CFU/g). The results showed that the dose of gambier leaf extract had no significant effect (P>0.05) on the water content and pH of chicken meat, but had a very significant effect (P<0.01) on the total microbial meat. Storage time had no significant effect (P>0.05) on water content, pH and the number of microbes in chicken meat. There was no interaction between the dose of gambier leaf extract and storage time.